Synthesis of Chalcone Derivative Compounds from 4 Chloro Acetophenone and In Silico Activity Test as Candidate Antidiabetic Compounds - nasution, Nurlaili; Jannah, Mifthahul; Syahri, Jufrizal (LPPM Universitas Muhammadiyah Riau, 2024)
This study aims to synthesize chalcone derivative compounds (E)-1-(4-Chlorophenyl)-3-(3-Hydroxyphenyl)Prop-2-En-1-One (CX) in alkaline conditions through a stirring method using a magnetic stirrer. 4 chloro acetophenone was reacted with 3 hydroxy benzaldehyde using ethanol p.a as a solvent and 60% KOH as a base catalyst. Furthermore, purification was carried out by recrystallization using ethanol p.a solvent and a yield of 72.67% was obtained. The purity test of the compound was carried out using TLC and melting point tests. Furthermore, the reaction compound was tested for activity as an antidiabetic in silico. In silico studies were carried out to predict the interaction of compounds with proteins (1GFY.pdb). In silico studies show that the cDOCKER energy value obtained by the original COL ligand is higher than the CX compound obtained. The results of the COL ligand docking with the 1GFY protein have a cDOCKER energy value of -49.4051 kcal/mol and have four hydrogen bonds that bind to the important amino acid residues Gly220, Arg221, Ser216 and Asp181. While the docking of the synthetic compound ligand (CX) produces a cDOCKER energy value of -29.293 kcal/mol and shows 3 hydrogen bonds to the important amino acid residues Ser216, Asp181 and Lys120. Based on these results, it is known that the CX compound has the potential to be used as an antidiabetic candidate compound.